Regional Cluster, Innovation and Export Performance: An Empirical Study - Prim,Alexandre Luis (2016)
Abstract Regional clusters and innovations in product and processes are found in the literature as important determinants of firms' export performance. However, this relationship is still controversial and very highly constrained by industry, and by regions. Based on a more integrative perspective, the aim of the present article is to investigate the role of agglomeration economies of a regional cluster on the export performance of firms. Furthermore, we will test the mediating effect of innovation and the extent by which the technological intensity of the industry can perform a moderating effect between the constructs. Based on a sample of 100 export companies operating in the manufacturing industries, we use structural equation modeling to estimate the determinants of export performance. The results reveal that the agglomeration economies of a regional cluster have been found determinant factors of the export performance, as well as a significant source to generate innovations by firms. However, we found no evidence between the innovations in products and processes and export performance. The results have also shown that there are no differences among technological intensity of the industries, suggesting that the firms will access agglomeration resources of regional cluster in a complementary way to their internal resources.